Cardiometabolic sex differences in adults born small for gestational age - Rodríguez-López, Mérida; Sepúlveda-Martínez, Álvaro; Bernardino, Gabriel; Crovetto, Francesca; Pajuelo, Carolina; Sitges, Marta; Bijnens, Bart; Gratacós, Eduard; Crispi, Fàtima (Frontiers in Cardiovascular Medicine, 2023)
Aim This study aimed to assess the cardiometabolic sex similarities and differences in adults born small for gestational age. Methods This study was an ambispective cohort study from a birth registry in Barcelona, Spain, including 523 adult participants (20–40 years-old) subdivided as born small for gestational age (SGA, if birth weight <10th centile) or adequate fetal growth for gestational age (AGA). Cardiometabolic health was assessed by echocardiography, electrocardiogram, blood pressure measurement, vascular ultrasound, anthropometric measurements, and serum glycemia and lipid profile. Stratified analyses by sex were performed by estimation of adjusted absolute difference (AAD) using inverse probability weighting. Results Compared with AGA, the stratified analyses by sex showed a more pronounced reduction in ejection fraction [AAD: female −1.73 (95% CI −3.2 to −0.28) vs. male −1.33 (−3.19 to 0.52)] and increment in heart rate [female 3.04 (0.29–5.8) vs. male 2.25 (−0.82 to 5.31)] in SGA females compared with SGA males. In contrast, a more pronounced reduction in PR interval [female −1.36 (−6.15 to 3.42) vs. male −6.61 (−11.67 to −1.54)] and an increase in systolic blood pressure [female 0.06 (−2.7 to 2.81) vs. male 2.71 (−0.48 to 5.9)] and central-to-peripheral fat ratio [female 0.05 (−0.03 to 0.12) vs. male 0.40 (0.17–0.62)] were mainly observed in SGA male compared with SGA female. Conclusions Sex differences were observed in the effect of SGA on cardiometabolic endpoints with female being more prone to cardiac dysfunction and male to electrocardiographic, vascular, and metabolic changes. Future research including sex-stratification data is warranted.